PENYELESAIAN HUKUM KEKERASAN DALAM RUMAH TANGGA SECARA NONLITIGASI DI KELURAHAN TANJUNG RAJA KABUPATEN OGAN ILIR PROVINSI SUMATERA SELATAN - Aprita, Serlika; Mulkan, Hasanal; Fakhriah, Syahriati; Hasyim, Yonani; Raspita, Desni; Afaf, Afaf; Roni, Abdul; Anggita, Jeni; Aldhini, Chindy (Devote: Jurnal Pengabdian Masyarakat Global, 2024)
Violence that occurs in the household is more often experienced by women who here act as wives or children who are victims, while the perpetrators are dominated by men who act as husbands or children. Domestic violence can be caused by various factors, both internal and external within the household. Internal factors that can trigger domestic violence include the character of the perpetrator of violence who tends to be emotional, economic dependence, third parties in the household, economic conditions, and poor communication. Changes in mindsets in society, especially women, have now changed, this is proven by the increasing number of divorce lawsuits in court. This change in thinking seems to form a view that marriage is not a sacred thing so there is no need to fight for its integrity if differences are discovered. However, the problem of domestic violence can be resolved outside of court (non-litigation). This legal counseling activity on the legal resolution of domestic violence committed by husbands against wives outside the court in Tanjung Raja Village, Ogan Ilir Regency, South Sumatra Province is expected to provide understanding to the public about actions that constitute domestic violence and their negative effects. Apart from that, it is hoped that with this outreach, the public will understand that Domestic Violence (KDRT) can be resolved first through non-litigation or outside of court.